Examination of Secondary School Students' Brand Awareness, Brand Loyalty, Brand Functions, and Factors Affecting Brand Loyalty According to Levels of Playing Team and Individual Sports - Ramazan Topuz; Hakan Salim Çağlayan; Yunus Altınbeyaz; Tuncay Sarıipek (Türk Spor ve Egzersiz Dergisi)
This research aims to determine the brand awareness, brand loyalty, brand functions, factors affecting brand loyalty and the preference criteria for product purchase (sports shoes) of secondary school students who do team and individual sports, and to determine whether these criteria make a difference according to the sports branches they play (team and individual). The sample of the study consists of a total of 250 students [n(male=185), n(female=65)], 150 of whom play team sports (football, volleyball, basketball, handball, folk dances) [n(male=118), n(female=32)] and 100 of whom play individual sports (taekwondo, kickboxing, badminton, fitness, wrestling, fencing) [n(male=67), n(female=33)], studying at high schools affiliated to the Konya Provincial Directorate of National Education in the first half of the 2019-2020 academic year. The mean age of the students participating in the research is 16.48±1.16, and the income level of their families is 2393.12 TL. It can be said that the income level of the families of the students participating in the research as of the period of application of the scales is at the level of the minimum wage. 34.8% (n=87) of the students participating in the research were in the 9th Grade, 27.2% (n=68) in the 10th Grade, 29.2% (n=73) in the 11th grade, and 8.8% (n=22) in the 12th grade. As data collection tools in the research, Brand Awareness Scale, Brand Loyalty Scale, Brand Functions Scale, Factors Affecting Brand Loyalty Scale, and Preference Criteria in Product Purchase Scale were used, which were translated into Turkish by Erdoğdu (2012) by making use of many studies in the literature and whose validity and reliability studies were conducted after language validity was ensured. As a result of the research, it was determined that the mean score of the students, who play team sports, from the related scales is higher than the students, who play individual sports. It was determined that the mean score of the students, who play team sports, from the Brand Awareness and Brand Loyalty Scale is significantly higher than the students who play individual sports, and it was also revealed that compared to the students playing individual sports, the mean scores of the students, who play team sports, from the "image function and social function" sub-dimensions of the Brand Functions Scale were significantly higher, that their mean scores from the "diversity/innovation seeking" sub-dimension of the Factors Affecting Brand Loyalty Scale were significantly higher, and that their mean scores from the "well-known brand/high image criterion, innovative/fashionable criterion, and social circle/friend criterion" sub-dimensions of the Scale of Preference Criteria for Product Purchase (Sports Shoes) were significantly higher.